Construction of recombinant K88 DNA with Ptac promoter - Holoda, E; Mikula, I (Folia microbiologica, 1994)
The gene encoding K88ab was localized on the 11.6 kb HindIII-HindIII fragment of 74 kb plasmid DNA of E. coli 7301. The smallest recombinant DNA producing the K88ab antigen was obtained by excision of the 5.15 kb EcoRI-EcoRI fragment from recombinant DNA composed of the 11.6 kb K88ab fragment in the pBR322 vector. The size of the smallest fragment was 6.5 kb. Expression of the K88ab antigen was controlled by the P1 promoter of the pBR322 vector. Substitution of promoter Ptac for promoter P1 made it possible to achieve expression of the K88ab antigen by E. coli MT. Substitution of promoter PL for promoter P1 failed to achieve expression of the K88ab antigen in the recipient strains used.
Keywords: prasata; Swine; Plasmids; Recombinant Fusion Proteins; antigeny povrchové; Cloning, Molecular; restrikční mapování; Restriction Mapping; klonování DNA; promotorové oblasti (genetika); Escherichia coli; proteiny fimbrií; bakteriofág lambda; regulace genové exprese u bakterií; rekombinantní fúzní proteiny; antigeny bakteriální; proteiny z Escherichia coli; Animals; Genes, Bacterial; Escherichia coli Proteins; zvířata; Promoter Regions, Genetic; Antigens, Surface; plazmidy; Antigens, Bacterial; Gene Expression Regulation, Bacterial; Bacteriophage lambda; bakteriální geny; Fimbriae Proteins